2018
DOI: 10.1093/aje/kwy125
|View full text |Cite
|
Sign up to set email alerts
|

Prolonged Leisure Time Spent Sitting in Relation to Cause-Specific Mortality in a Large US Cohort

Abstract: The majority of leisure time is spent in sedentary behaviors such as television viewing. Studies have documented that prolonged leisure-time sitting is associated with higher risk of mortality-total, cardiovascular disease, cancer, and "all other causes"-but few have examined the "other" causes of death in detail. To examine associations of leisure-time sitting with risk of specific causes of death, we analyzed data from the Cancer Prevention Study II (CPS-II) Nutrition Cohort, a prospective US cohort includin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
27
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
3
1

Relationship

1
9

Authors

Journals

citations
Cited by 50 publications
(27 citation statements)
references
References 23 publications
0
27
0
Order By: Relevance
“…However, the CPS-II physical activity and sitting time items are very similar to the items validated in the Nurses' Health Study II (18). These measures have also been associated with various cancers in this cohort (19). Another limitation is the relatively small number of CML and AML cases.…”
Section: Discussionmentioning
confidence: 84%
“…However, the CPS-II physical activity and sitting time items are very similar to the items validated in the Nurses' Health Study II (18). These measures have also been associated with various cancers in this cohort (19). Another limitation is the relatively small number of CML and AML cases.…”
Section: Discussionmentioning
confidence: 84%
“…In this context, inactivity is not just a lack of the positive effects of being physically active, strong research has shown that prolonged sitting results in negative consequences to health (risk for Type 2 diabetes, obesity, cardiovascular disease, etc.) with distinct mechanistic underpinnings [44,46,47]. Akin to the situation with adding exercise, however, subtracting movement to create a “sedentary” research condition cannot be separated from the energy balance context.…”
Section: Inactivity Energy Balance and Insulin Sensitivitymentioning
confidence: 99%
“…Prolonged unbroken sitting time (e.g., watching TV at home and work at the office) is related to the risk of various disease outcomes in healthy people, including obesity, type 2 diabetes, cardiovascular disease, and all-cause mortality [1,2,3,4,5]. Performing physical activity including non-exercise activity thermogenesis (NEAT) [6] and increasing daily total energy expenditure (EE) have contributed significantly to health outcomes [7].…”
Section: Introductionmentioning
confidence: 99%